MENILIK PREFERENSI PEKERJAAN (JOB PREFERENCES ) PADA KELOMPOK GENERASI X - Yustinus Yuniarto (Business Management Journal, 2019)
Organizations in the present era prioritize smart work rather than hard work. Not infrequently the group has the character of wanting everything to be achieved instantly or in a shorter time. Based on data from the Central Bureau of Statistics of the Republic of Indonesia, in 2016 the number of workers from the X generation group was almost the same as the number of millennial workers. The Babby Boomers generation group continued to decline in number. Slowly, the X generation of workers will also experience the same thing. This phenomenon has been marked by the arrival of the millennial generation as a workforce that increasingly makes the composition of the generation of Babby Boomers diminishing in 2014 and 2016). This explains that the transition of generations of workers is  impossible to avoid or in other words the law of demand and supply applies to human resources in Indonesia. This study aims to analyze job preferences (job preferences) in groups of generation X workers based on work values. This research is quantitative research using multiple  regression analysis and SPSS. The error rate in this study uses the magnitude of 5%. Using 102 samples of this study explains that Job Preference is partially influenced by factors of self-realization and welfare guarantees but Job Preference for gen-X workers is not influenced by factors of work environment harmony and material factors. Simultaneously, Job Preference for gen-X workers is influenced by the factors of material conditions, selfrealization,  harmonization of the work environment and welfare factors.Keywords: job preference, work value, work environment